Sobranie sočinenij. Teil 3: Dvenadcat' Dram Herausgegeben von Bernhard Lauer und Ulrich Steltner - Sologub, Fëdor (Slavistische Beitraege, 2000)
In the present third volume of the edition of works of the Russian symbolist Fedor Sologub (1863-1927) twelve of his dramas are reprinted, some of them again for the first time after eighty to one hundred years.